Effect of Cutting Tool Rake and Inclination Angles and Feeding Method on Cutting Force and Surface Quality in Single-point Threading - Abdalrahman, Rzgar Mhammed; Rostam, Sarkawt; Deboucha, Abdelhakim (Kurdistan Journal of Applied Research, 2025)
Single-point threading is the most common and useful thread machining technique. It is mostly applicable in situations which require threaded pieces with certain diameters and high quality on low machinability materials. The process has problems of surface quality and power consumption because of lack of information regarding the effect of the tool’s rake and inclination angles and feeding method on surface quality and cutting forces as a function of cutting power. This study investigates influences of tool infeed method, rake, and inclination angles on surface quality of thread flanks and the cutting forces generated. Three levels of 0°, 2°, and 3.5° as well as -6°, 0°, and 1° were considered for tool inclination and rake angles, respectively, with the two most common tool infeed methods of radial and flank infeed. Accordingly, eighteen tests were conducted by cutting metric screws of 5 mm thread pitch and triangular profile on ST45 carbon steel bar. The cutting speed, number of cutting passes, and infeed amount in each pass were maintained constant during each test. The threads were cut by P-10 type carbide insert on a test rig that involved a medium-sized lathe. Results presented that the highest inclination angle of 3.5° produces lowest surface roughness of about 0.5 and 0.45 μm and cutting force of 1850 N and 2200 N in the radial and flank infeed methods, sequentially. Also, a rake angle of 0° provides better and more equal surface finish on the both thread flanks. A high productive approach for the single-point threading with high quality was deduced.